A Tuboovarian Abscess Associated with a Ruptured Spleen. (24th January 2016) - Li, Jennifer S.; Sheele, Johnathan Michael
Abstract : We report the first case of a tuboovarian abscess complicated by a ruptured spleen. Our patient was a 27-year-old female with human immunodeficiency virus (HIV) who presented to the emergency department (ED) with complaints of urinary symptoms and diarrhea. After being diagnosed with a tuboovarian abscess (TOA), she received antibiotics and was admitted to the gynecology service. Shortly thereafter she developed hemorrhagic shock, necessitating a splenectomy and salpingooophorectomy from a ruptured spleen.